Smartphone Usage and Psychological Well-being among Malaysian University Students. - Yoke Yong, Chen (EBSCO, 2021)
Smartphone has become indispensable in individual daily life in which excessive used of smartphone might interfere with one’s psychological well-being. Thus, it is crucial to understand how smartphones give impact on the psychological well-being especially among young people. The objective of present research was to investigate the smartphone usage among students in Universiti Malaysia Sarawak (UNIMAS) and its relation with psychological well-being. The present study was a cross-sectional study and there were 274 undergraduates from UNIMAS had been recruited, age ranged from 19 to 28 years old, with 28.5% males and 71.5% females. Smartphone usage questionnaire, Social Anxiety Questionnaire for Adults (SAQ-A30), Fear of Missing Out Scale (FOMOs), Center for Epidemiologic Studies-Depression Scale (CESD), and Three-Item Loneliness Scale were used in the present study. The result showed that UNIMAS students spent approximately 8 hours (SD = 4.26) per day, on Instagram, followed by Twitter, Facebook, WhatsApp, and Wechat. Depressive scores were significantly associated with hours spent on smartphones daily. The result also showed that texting significantly associated with SAQ while social networking and gaming were significantly associated with FOMO scores. FOMO was mediating the hours spent on smartphone and depression scores. When the participants used their smartphone in a day was also mediated by FOMO contributing to their social anxiety scores. The results have practical implications for policymaker and advertisement that is more population targeted in promoting their products or deliver information.